Penerapan evidence-based practice nursing program intradialytic flexsibility exercise range of mation terhadap fatigue pada pasien chronic kidney disease yang menjalani hemodialisa - Siswandi, Iyar; Sofiani, Yani; Barus, Sada Ukur; Agung, Rizki Nugraha; Septiawantari, Rani (Holistik Jurnal Kesehatan, 2025)
Background: Chronic Kidney Disease (CKD) is one of the leading causes of global morbidity and mortality. Patients undergoing hemodialysis often experience fatigue, which significantly affects their quality of life, productivity, and psychological well-being. One of the non-pharmacological interventions that can be applied is intradialytic flexibility exercise in the form of range of motion (ROM). Purpose: To determine the effect of intradialytic flexibility exercise range of motion on fatigue levels among CKD patients undergoing hemodialysis. Method: A quasi-experimental study using a one-group pre-post test design was conducted from May to July 2025 at Al Ihsan Regional General Hospital, West Bandung. Purposive sampling was used to select 18 participants. The independent variable in this study was the Intradialytic Flexibility Exercise Range of Motion Program, while the dependent variable was the level of fatigue. Data analysis was performed using univariate analysis in the form of frequency distribution and bivariate analysis using the Cochran test. Translated with DeepL.com (free version) Results: Before the intervention, 77.8% of participants experienced severe fatigue. After 8 weeks of intervention, all participants (100%) showed a decrease in fatigue to a mild category. Statistical analysis indicated a significant difference in fatigue levels before and after the intervention (p < 0.05). Conclusion: Intradialytic flexibility exercise range of motion is effective in reducing fatigue levels among CKD patients undergoing hemodialysis. This intervention can be considered a non-pharmacological nursing strategy to improve patients’ quality of life.   Keywords: Chronic Kidney Disease; Fatigue; Hemodialysis; Intradialytic Exercise; Range of Motion.   Pendahuluan: Penyakit ginjal kronis (CKD) merupakan salah satu penyebab utama morbiditas dan mortalitas global. Pasien CKD yang menjalani hemodialisis sering mengalami kelelahan (fatigue) yang berdampak pada kualitas hidup, produktivitas, dan kesehatan mental. Salah satu intervensi non-farmakologis yang dapat diterapkan adalah intradialytic flexibility exercise berupa range of motion (ROM). Tujuan: Untuk mengetahui pengaruh penerapan intradialytic flexibility exercise range of motion terhadap tingkat kelelahan pada pasien CKD yang menjalani hemodialisa. Metode: Penelitian quasi experimental dengan metode one group pre-posttest design, dilaksanakan pada Mei-Juli 2025 di RSUD Al Ihsan, Bandung Barat. Teknik pengambilan sampel menggunakan purposivel sampling dengan jumlah sampel yang digunakan sebanyak 18 partisipan. Variabel independen dalam penelitian ini adalah Program Intradialytic Flexibility Exercise Range of Motion, sedangkan variabel dependen ialah tingkat kelelahan. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi dan bivariate menggunakan uji Cochran. Hasil: Sebelum intervensi, 77.8% partisipan mengalami fatigue berat. Setelah 8 minggu intervensi, seluruh partisipan (100%) mengalami penurunan tingkat fatigue menjadi kategori ringan. Hasil uji statistik menunjukkan adanya perbedaan signifikan tingkat fatigue sebelum dan sesudah intervensi (p < 0.05). Simpulan: Penerapan intradialytic flexibility exercise range of motion efektif menurunkan tingkat kelelahan pada pasien CKD yang menjalani hemodialisa.   Kata Kunci: Chronic Kidney Disease; Fatigue; Hemodialisa; Intradialytic Exercise; Range of Motion.